Photophysical and photochemical trends in tricarbonyl rhenium(I) N- heterocyclic carbene complexes - Vaughan, J.; Reid, Brodie; Wright, Phillip; Ramchandani, S.; Skelton, B.; Raiteri, Paolo; Muzzioli, S.; Brown, David; Stagni, S.; Massi, Massimiliano (American Chemical Society, 2014)
A family of tricarbonyl Re(I) complexes of the formulation fac-[Re(CO)3(NHC)L] has been synthesized and characterized, both spectroscopically and structurally. The NHC ligand represents a bidentate N-heterocyclic carbene species where the central imidazole ring is substituted at the N3 atom by a butyl, a phenyl, or a mesityl group and substituted at the N1 atom by a pyridyl, a pyrimidyl, or a quinoxyl group. On the other hand, the ancillary L ligand alternates between chloro and bromo. For the majority of the complexes, the photophysical properties suggest emission from the lowest triplet metal-to-ligand charge transfer states, which are found partially mixed with triplet ligand-to-ligand charge transfer character. The nature and relative energy of the emitting states appear to be mainly influenced by the identity of the substituent on the N3 atom of the imidazole ring; thus, the pyridyl complexes have blue-shifted emission in comparison to the more electron deficient pyrimidyl complexes. The quinoxyl complexes show an unexpected blue-shifted emission, possibly occurring from ligand-centered excited states.No significant variations were found upon changing the substituent on the imidazole N3 atom and/or the ancillary ligand. The photochemical properties of the complexes have also been investigated, with only the complexes bound to the pyridyl-substituted NHC ligands showing photoinduced CO dissociation upon excitation at 370 nm, as demonstrated by the change in the IR and NMR spectra as well as a red shift in the emission profile after photolysis. Temperature-dependent photochemical experiments show that CO dissociation occurs at temperatures as low as 233 K, suggesting that the Re–C bond cleaves from excited states of metal-to-ligand charge transfer nature rather than thermally activated ligand field excited states. A photochemical mechanism that takes into account the reactivity of the complexes bound to the pyridyl-NHC ligand as well as the stability of those bound to the pyrimidyl- and quinoxyl-NHC ligands is proposed.